Millennial backpackers and risks in travel: a typological approach - Jabłonkowska, Jolanta Barbara; Stankiewicz, Bogusław (Turyzm/Tourism, 2020)
In the research undertaken, the analysis categorised risk in the experience of the millennial generation of backpackers. An attempt was made to systematise it on the basis of the cognitive as well as emotional characteristics presented by the respondents. The research was conducted between 2018-2020. A non-random selection was used to acquire respondents called snowball sampling. 409 Polish millennial backpackers were found and interviewed online, and from this code keys were then extracted, assigned to meaningful categories, and thematic ranges were defined. The analysis of the collected qualitative material was used to establish a typology of risk for millennial backpacking. Analysis of the collected material on backpacking allowed five coded risk categories to be extracted. The first one was the backpacker's attitude towards travel; the second a search for autonomy and independence; the third selective calculation in terms of ‘profit and loss’, the balance determining behaviour; the fourth connected with the emotional needs of backpackers and the search for impressions; the fifth with external conditions involving risk related to environmental and cultural features of the reception area. Typological systematization of risk in backpacking allows the needs of this groups of travellers to be understood and service provision to be adapted to the requirements of a particular generation.